(untitled) (Педагогіка вищої та середньої школи, 2008)
Developped scholastic-checking programs on the base of text editor Microsoft Word and program of testing "Assistent”. Using is didactic-checking programs in conditions of transition on credit-module system accordingly Bulougne process renders the assistance to increasing to efficiency of study by students of technical discipline.